Ads 468x60px

Operations on Functions: Part 1 - Addition and Subtraction

 Addition of Functions
`(f+g)(x) = f(x) + g(x)`

Note: Terms can only be added or subtracted if they are similar – when they have the same variable part (literal coefficient).  For example, you can add/subtract `3x^2` and `-2x^2` because they have the same variable part `x^2` (including the exponent of the variables). You cannot add/subtract `-7x` and `4x^2` because they are not similar terms.

Given:                   `f(x) = 3x+4`                                   `g(x)= 2x-7`

1. `(f+g)(x)`
`=> (f+g)(x) = f(x) + g(x)`
`=> = (3x + 4) + (2x - 7)`
`=> = 3x + 2x + 4 - 7`
`=> = 5x - 3`

2. `(g+f)(-3)`
`=> (g+f)(-3) = g(-3) + f(-3)`
`=> = (2x - 7) + (3x + 4)`
`=> = 2(-3) - 7 + 3(-3) + 4`
`=> = -6 - 7 - 9 + 4`
`=> = -18`

Alternatively, you can solve `g(-3)` and `f(-3)` individually and then add their results.

`=> (g+f)(-3) = g(-3) + f(-3)`

for `g(-3)`
`=> g(-3)= 2x - 7`
`=> = 2(-3) - 7`
`=> = -6 - 7`
`=> = -13`

for `f(-3)`
`=> f(-3)= 3x + 4`
`=> = 3(-3) + 4`
`=> = -9 + 4`
`=> = -5`

Thus,
 `=> (g+f)(-3) = g(-3) + f(-3)`
`=>  = -13 + -5`
`=>  = -18`

Subtraction of Functions `(f-g)(x) = f(x) - g(x)`

Note: Terms can only be added or subtracted if they are similar – when they have the same variable part (literal coefficient).  For example, you can add/subtract `3x^2` and `-2x^2` because they have the same variable part `x^2` (including the exponent of the variables). You cannot add/subtract `-7x` and `4x^2` because they are not similar terms.

Given:                   `f(x) = 3x+4`                                         `g(x)= 2x-7`

3. `(f-g)(x)`
`=> (f-g)(x) = f(x) - g(x)`
`=> = (3x + 4) - (2x - 7)` 
Note: When you have a negative sign `-` before a parenthesis `(`, what you do is flip the signs of all the terms inside the parenthesis. (i.e. positive becomes negative and vice-versa.)  
`=> = 3x + 4 - 2x + 7`  (Notice how `2x` becomes `-2x` and `-7` becomes `+7`)
`=> = 3x - 2x + 4 + 7`
`=> = x + 11`

4. `(g-f)(-2)`
`=> (g-f)(-2) = g(-2) - f(-2)`
`=> = (2x - 7) - (3x + 4)`
`=> = 2x - 7 - 3x - 4`
`=> = 2(-2) - 7 - 3(-2) - 4`
`=> = -4 - 7 + 6 - 4`
`=> = -9`

Alternatively, you can solve `g(-2)` and `f(-2)` individually and then subtract their results.

`=> (g-f)(-2) = g(-2) - f(-2)`

for `g(-2)`
`=> g(-2)= 2x - 7`
`=> = 2(-2) - 7`
`=> = -4 - 7`
`=> = -11`

for `f(-2)`
`=> f(-2)= 3x + 4`
`=> = 3(-2) + 4`
`=> = -6 + 4`
`=> = -2`

Thus,
 `=> (g-f)(-2) = g(-2) - f(-2)`
`=>  = (-11) - (-2)`
`=>  = -11 + 2`
`=>  = -9`

EXERCISES

Given: `f(x) = -3x + 7`                               `g(x) = 2x + 4`
  1. `(g+f)(x)`

    `=> (g+f)(x) = g(x) + f(x)`
    `=> = (2x + 4) + (-3x + 7)`
    `=> = 2x - 3x + 4 + 7`
    `=> = -x + 11`
  2. `(f+g)(-2)`

    `=> (f+g)(-2) = f(-2) + g(-2)`
    `=>  = f(-2) + g(-2)`

    For `f(-2)`
    `=> f(-2) = -3x + 7`
    `=> = -3(-2) + 7`
    `=> = 6 + 7`
    `=> = 13`

    For `g(-2)`
    `=> g(-2) = 2x + 4`
    `=> = 2(-2) + 4`
    `=> = -4 + 4`
    `=> = 0`

    `=>  = f(-2) + g(-2)`
    `=>  = 13 + 0`
    `=>  = 13`
  3. `(f+g)(x+7)`

    `=> (f+g)(x+7) = f(x+7) + g(x+7)`

    For `f(x+7)`
    `=> f(x+7) = -3x + 7`
    `=> = -3(x + 7) + 7`
    `=> = -3x - 21 + 7`
    `=> = -3x - 14`

    For `g(x+7)`
    `=> g(x+7) = 2x + 4`
    `=> = 2(x+7) + 4`
    `=> = 2x + 14 + 4`
    `=> = 2x + 18`

    `=>  = f(x+7) + g(x+7)`
    `=>  = -3x - 14 + 2x + 18`
    `=>  = -x + 4`
  4. `(g-f)(3)`

    `=> (g-f)(3) = g(3) - f(3)`

    For `g(3)`
    `=> g(3) = 2x + 4`
    `=> = 2(3) + 4`
    `=> = 6 + 4`
    `=> = 10`

    For `f(3)`
    `=> f(3) = -3x + 7`
    `=> = -3(3) + 7`
    `=> = -9 + 7`
    `=> = -2`

    `=>  = g(3) - f(3)`
    `=>  = 10 - (-2)`
    `=>  = 10 + 2`
    `=>  = 12`
  5. `(f-g)(2x)`

    `=> (f-g)(2x) = f(2x) - g(2x)`

    For `f(2x)`
    `=> f(2x) = -3x + 7`
    `=> = -3(2x) + 7`
    `=> = -6x + 7`

    For `g(2x)`
    `=> g(2x) = 2x + 4`
    `=> = 2(2x) + 4`
    `=> = 4x + 4`
    `=> = 4x + 4`

    `=>  = f(2x) - g(2x)`
    `=>  = (-6x + 7) - (4x + 4)`
    `=>  = -6x + 7 - 4x - 4`
    `=>  = -10x + 3`
  6. `(g-f)(1/6)`

    `=> (g-f)(1/6) = g(1/6) - f(1/6)`

    For `g(1/6)`
    `=> g(1/6) = 2x + 4`
    `=> = 2(1/6) + 4`
    `=> = 1/3 + 4`
    `=> = 13/3`

    For `f(1/6)`
    `=> f(1/6) = -3x + 7`
    `=> = -3(1/6) + 7`
    `=> = -1/2 + 7`
    `=> = -13/2`

    `=>  = g(1/6) - f(1/6)`
    `=>  = 13/3 - (-13/2)`
    `=>  = 13/3 + 13/2`
    `=>  = (13(2) + 13(3))/6`
    `=>  = 65/6`


3 comments:

  1. Great Mathematics tricks been shared by you. I am glad to find your blog, I went through the page and found many new and important things in the blog. Thank you for taking time to share these details with us. Best home tutor services are provided by TheTuitionTeacher in Delhi.
    Home Tutors in Delhi | Home Tutors Delhi

    ReplyDelete
  2. This comment has been removed by the author.

    ReplyDelete

 

Mission

Our mission is to create an open, constructive learning environment where diverse tutoring techniques address individual academic needs. We empower students to become confident, effective, and independent learners, equipping them with essential skills in an atmosphere that fosters growth, resilience, and a lifelong love for learning.

Vision

A transformative institution, delivering quality tutoring services that guarantee academic success, positively impacting the world child by child.